Following Djuna : women lovers and the erotics of loss - Allen, Carolyn, 1943- (Theories of representation and difference., 1996)
Following Djuna reads contemporary novelists in the tradition of Djuna Barnes, arguing for the importance of women's fiction in understanding women's erotics - emotional and sexual exchanges between women. Barnes's Nightwood, with its experimental form and passionate language, has made its mark on contemporary writers, and Carolyn Allen argues that Harris, Winterson, and Brown continue Barnes's explorations of obsession, loss, excess, and power between women lovers. Allen stresses the importance of difference in lovers who are "like", and the influence of memory in the making of desire. At the same time, she illuminates the ongoing trade-offs between passion and comfort, and between loss and discovery as crucial to the intensity of women's erotics